Prosedur Coronary Angiography (CAG) Pada Pasien Dengan Kasus Mitral Stenosis (MS) Severe - Muh Reza Mappagau; Kusman Kusman (Journal of Educational Innovation and Public Health, 2024)
Mitral stenosis (MS) is a heart valve disorder in which the mitral valve (located between the left atrium and left ventricle) becomes narrowed or hardened, blocking blood flow from the left atrium to the left ventricle. Coronary angiography (CAG) is an invasive diagnostic technique used to evaluate the condition of the coronary blood vessels in patients with acute transmural myocardial infarction (MI). Coronary Angiography (CAG) examination in cases of Severe Mitral Stenosis (MS) Severe involves patient preparation, equipment preparation, medical team, examination procedures, post-action care, description of examination results, and its role in the management of Severe (MS) Patient preparation involves patient education about procedures, fasting before examination, renal function checks, medication adjustments, vascular access preparation, discussion of contrast agents, and vital monitoring. Narrowing of the heart's mitral valve is a pathological condition in which this narrowing inhibits blood flow from the left atrium to the left ventricle. Coronary angiography (CAG) plays an important role in clinical evaluation and therapeutic planning. Background: Mitral stenosis (MS) is a heart valve disorder in which the mitral valve (located between the left atrium and left ventricle) becomes narrowed or hardened, blocking blood flow from the left atrium to the left ventricle. This can increase pressure in the left atrium and reduce the amount of blood pumped throughout the body. Because MS is associated with increased left atrial pressure and can affect overall cardiac hemodynamics, it is important to understand how this condition may interact with coronary artery pathology. This research method is a literature review study, where literature exploration is carried out in various databases with keywords such as Coronary Angiography, Severe Mitral Stenosis Cases. Results: Coronary Angiography (CAG) examination in cases of Severe Mitral Stenosis (MS) Severe involves patient preparation, equipment preparation, medical team, examination procedures, post-action care, description of examination results, and their role in the management of (MS) Severe Patient preparation involves patient education about the procedure, fasting before examination, renal function testing, medication adjustments, vascular access preparation, discussion of contrast agents, and vital monitoring. Severe (MS) patients require special attention in this preparation. Equipment preparation includes a stable catheterization table, a fluoroscopic imaging system, various types of catheters, appropriate contrast agents, resuscitation equipment, pre-procedure medications, and hemostasis equipment. The medical team involved in CAG examination in Severe (MS) patients involves an interventional cardiologist, radiological technologist, catheterization nurse, catheterization technician, and additional support personnel such as the anesthesia team and resuscitation team. The examination procedure includes patient preparation, vascular access, catheter insertion into the coronary arteries, evaluation and imaging of the coronary arteries, and completion of the procedure. CAG examination has an important role in the detection of coronary artery disease. CAG examination in patients with (MS) Severe requires careful preparation and involves the collaboration of a well-coordinated medical team to provide optimal results and a significant contribution in the management of (MS) Severe. Conclusion: Narrowing of the mitral valve, severe mitral stenosis (MS) is a pathological condition where this narrowing inhibits blood flow from the left atrium to the left ventricle. This condition is most often caused by rheumatic heart disease, which results in inflammation and ultimately thickening and narrowing of the mitral valve. Coronary Angiography (CAG) examination in Severe Mitral Stenosis (MS) cases has an important role in detecting coronary artery disease.